Pesca artesanal de peixes vermelhos entre o litoral do Ceará e Piauí: etnoconhecimento e avaliação de estoque como subsídio para a conservação - Silva, Carlos Eduardo Lira dos Santos (2024)
Artisanal fishing provides food and employment for more than 31 million fishermen, mainly in developing countries located in tropical regions. Worldwide, it contributes half of the fishing effort and more than a quarter of the volume of catches. Among the resources targeted by fisheries, the species of the Lutjanidae family are outstanding for their high economic value, which has lead to population declines and signs of overfishing for some species. With an emphasis on lutjanids, this thesis aimed to characterize fishing, assess the sustainability of catches, determine population parameters and analyses the traditional knowledge of artisanal fishermen in the Bitupitá district, Barroquinha, located in the furthest west of Ceará. Landings were monitored monthly between March 2022 and February 2023, representing around 20 vessels or 10% of landings. The specimens of lutjanids were measured and weighed in situ and those of the vermilion snapper Rhomboplites aurorubens were bought to study its reproductive biology. After the monitoring, the fishermen were interviewed using surveys to infer their ethnographic knowledge. At the Fisheries Bioecology Laboratory - BIOPESCA (UFDPar), the specimens were measured, and the gonads were removed for histological procedures. Snapper fishing takes place in 8 and 10 m long canoes, with 3 and 4 fishermen using vertical longlines. The trip lasts between three and six days, with the catch occurring mainly at night and at low tide. A total of 243 landings were monitored, with an average production of 190 kg/canoe and total production/year estimated at 500 tons. Fishing takes place on fishing grounds located on the continental shelf and upper slope. A total of 47 species of fish were recorded in this fishery, six of which are lutjanid species, which are considered a target of the fishery. The yellowtail snapper Lutjanus chrysurus is the species with the highest production. The red snapper L. purpureus, lane snapper L. analis and mutton snapper L. jocu have high vulnerability values, due to the considerable abundance of immature specimens in the landings, high fishing mortality and alarming spawning potential ratio (SPR) values. To determine the reproductive parameters of R. aurorubens, 423 specimens were acquired, with a sex ratio similar to 1:1 (M:F). The highest IGS and IHS values were recorded in the rainy season. The length at sexual maturity was 18.9 cm and the average fecundity was 135,112 oocytes. The species spawns in batches. This study provides important and pioneer data on the status of lutjanid populations in the region, which can support control actions, favoring fisheries management. A change in the hook size used is suggested, avoiding the capture of juvenile specimens.